Light-activated bifunctional nanozymes based on three-component covalent organic frameworks for colorimetric and ratiometric fluorescence dual-mode detection of alkaline phosphatase - Hu, Cong; Li, Guorong; Xue, Yuandi; Liu, Jin; Cai, Zongwei; Lin, Zian (Sensors and actuators. B, Chemical, 2025)
Nanozymes-based optical sensors are widely used in the field of disease diagnosis, but most of the metal-based nanomaterials with peroxidase-like would not only require the addition of unstable and slightly toxic hydrogen peroxide but also often be affected by their own oxidase-like activity leading to the problems such as poor reproducibility and environmental pollution. Moreover, single-mode biosensors are subject to signal instability, which can lead to false-positive or false-negative results. Hence, we synthesized two three-component covalent organic frameworks (COFs) with the oxidase-like and ascorbate oxidase-like activities using benzo[1,2-b:3,4-b':5,6-b'']trithiophene-2,5,8-tricarboxaldehyde (BTT) and 1,3,5-tris(4-formylphenyl)benzene (TFPB) as the nodes, and 1,4-diaminobenzene (PA) and 4,4-diaminodiphenyl (BD) as the linker units. Both three-component COFs had narrow band gaps (2.16 eV and 2.27 eV), excellent electron transport properties, and high enzyme-like specific activities (4.32 U mg−1 and 1.82 U mg−1). Based on these, a colorimetric and ratiometric fluorescence dual-mode cascade catalytic platform was developed to detect the activity of alkaline phosphatase (ALP), a marker for diseases such as liver and bone. The constructed analytical methods had a detection limit as low as 0.10 U L−1 and were successfully used to detect ALP levels in human serum. This work also provides a new idea for developing an efficient multimodal detection and evaluation platform using nanozymes based on novel COFs. •Two three-component donor-π-acceptor COFs were successfully synthesized.•The COFs exhibited good light-activated oxidase-like and ascorbate oxidase-like activities.•A colorimetric and ratiometric fluorescence dual-mode cascade catalytic platform was constructed.•The constructed cascade assay platform could be used to detect ALP levels in serum.